2016
DOI: 10.1111/caim.12182
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Focus, Task Engagement and Divergent Thinking

Abstract: We investigate the effect of individuals’ regulatory focus on divergent thinking performance. We analysed 3576 ideas, generated by 341 English‐speaking adults who participated in two separate divergent thinking tasks. A promotion focus results in higher levels of creative potential. Based on regulatory fit theory, we find that task engagement mediates the positive effect of a promotion focus on creative potential. Our findings are robust regardless whether fluency, flexibility or uniqueness is used as the crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In other words, motivational states are not universally effective; rather, the effectiveness of a motivational state often depends on the particular demands of a situation (see also Bonanno & Burton, 2013). For example, whereas eager motivational states (enthusiastically seeking opportunities for gains) tend to enhance performance in situations requiring divergent thinking (e.g., a creative brainstorming task), vigilant motivational states (carefully protecting against potential losses) are more likely to enhance performance in situations characterized by convergent thinking (e.g., logic problems; Beuk & Basadur, 2016; Semin, Higgins, de Montes, Estourget, & Valencia, 2005).…”
Section: When People Regulate Motivation What Are They Regulating?mentioning
confidence: 99%
“…In other words, motivational states are not universally effective; rather, the effectiveness of a motivational state often depends on the particular demands of a situation (see also Bonanno & Burton, 2013). For example, whereas eager motivational states (enthusiastically seeking opportunities for gains) tend to enhance performance in situations requiring divergent thinking (e.g., a creative brainstorming task), vigilant motivational states (carefully protecting against potential losses) are more likely to enhance performance in situations characterized by convergent thinking (e.g., logic problems; Beuk & Basadur, 2016; Semin, Higgins, de Montes, Estourget, & Valencia, 2005).…”
Section: When People Regulate Motivation What Are They Regulating?mentioning
confidence: 99%
“…Fluency, flexibility, and uniqueness are often used as measures of creativity (Beuk & Basadur, 2016; Guilford, 1950). Fluency is measured as the number of ideas per respondent; flexibility is measured as the total number of distinct categories of thinking these ideas represent; and originality is defined as a low frequency of occurrence of ideas when compared with all ideas given (see, e.g., Beuk & Basadur, 2016). Other researchers measure creativity on an anchored scale, from “very uncreative” to “very creative” (Grant & Berry, 2011; Naidoo, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the literature suggested that RFT affects individuals’ attitudes and behaviors ( Higgins and Cornwell, 2016 ). An example is given in the study by Beuk and Basadur (2016) , who found that promotion focus had a positive effect on task engagement.…”
Section: Related Workmentioning
confidence: 99%
“…Whereas individuals in a promotion focus are eager to attain advances and gains, individuals in a prevention focus are vigilant to ensure safety and avoid losses. As such, RFT has been found to positively impact creativity ( Baas et al, 2008 ) and idea generation ( Beuk and Basadur, 2016 ) and to induce longer social engagement ( Agrigoroaie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%